Work Table Product Design Of Multifunctional Work Table For Workers In Limited Space (Case Study: Puri Surya Jaya Cluster, Sidoarjo) - Arvin Ray Anggasta; Yosef Richo Adrianto; Darwin Yuwono; Martinus Sony Erstiawan (Fakultas Industri Kreatif Universitas Surabaya, 2024)
A work desk is a piece of furniture used in the daily life of an employee in an office. Work desks require a large enough space for computers, laptops, and writing, offices located in large buildings have no problem in the size of the room for a special work desk but offices located at home cannot provide enough space for work desks because of the narrow space, therefore home offices use small minimalist desks to save space. To answer the lack of a narrow home office workspace, a multifunctional work desk product was designed that can save space. The making of this multifunctional table is intended to help in work, especially in home offices because of its simple design and smaller dimensions that save space and are easy to move.